Aneurysm of the Left Sinus of Valsalva: An Unusual Presentation - Hoganson, Neil E. (1990)
Unruptured aneurysms of the left sinus of Valsalva are extremely rare, and their clinical features are not well-documented in the literature. We describe an unusual case in which an unruptured aneurysm of the left sinus of Valsalva associated with previously undiagnosed Marfan syndrome caused extrinsic compression of the esophagus, resulting in dysphagia unrelated to the type or timing of meals. Our report focuses on the initial clinical presentation, as well as the diagnosis and management of this rare lesion. (Texas Heart Institute Journal 1990;17:245-8)